2007
DOI: 10.1016/j.bbr.2006.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Lasting changes in neuronal activation patterns in select forebrain regions of aggressive, adolescent anabolic/androgenic steroid-treated hamsters

Abstract: Repeated exposure to anabolic/androgenic steroids (AAS) during adolescence stimulates high levels of offensive aggression in Syrian hamsters. The current study investigated whether adolescent AAS exposure activated neurons in areas of hamster forebrain implicated in aggressive behavior by examining the expression of FOS, i.e., the protein product of the immediate early gene c-fos shown to be a reliably sensitive marker of neuronal activation. Adolescent AAS-treated hamsters and sesame oil-treated littermates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 79 publications
(132 reference statements)
4
24
1
Order By: Relevance
“…E2 did not increase the number of vocalizations, so the increase in ZENK-IR cannot be attributed to the birds' own vocal behavior (see also Maney et al, 2003Maney et al, , 2006. This result is consistent with other reports of steroidinduced IEG expression (Insel, 1990;Hyder et al, 1994;Johansson-Steensland et al 2002;Dimeo and Wood, 2006;Ricci et al, 2007;Tremere et al, 2009). Like Tremere et al (2009), who administered E2 locally in NCM in zebra finches, we found that E2 was as effective as song stimulation at inducing ZENK-IR and that song presentation did not enhance it further.…”
Section: Discussionsupporting
confidence: 93%
“…E2 did not increase the number of vocalizations, so the increase in ZENK-IR cannot be attributed to the birds' own vocal behavior (see also Maney et al, 2003Maney et al, , 2006. This result is consistent with other reports of steroidinduced IEG expression (Insel, 1990;Hyder et al, 1994;Johansson-Steensland et al 2002;Dimeo and Wood, 2006;Ricci et al, 2007;Tremere et al, 2009). Like Tremere et al (2009), who administered E2 locally in NCM in zebra finches, we found that E2 was as effective as song stimulation at inducing ZENK-IR and that song presentation did not enhance it further.…”
Section: Discussionsupporting
confidence: 93%
“…This is in contrast with other studies showing a positive relationship between the display of aggression and lateral septum activation [Halasz et al, 2002a;Ricci et al, 2007]. Moreover, a pharmacologically induced decrease in aggression was associated with a decrease in neuronal activation of the lateral septum [Trainor et al, 2006].…”
Section: Neuronal Circuits/neuronal Activationcontrasting
confidence: 55%
“…In a number of previous reports, we have shown that in the Syrian hamster administration of AAS throughout the developmental period of adolescence produces hamsters with escalated levels of offensive aggressive behavior (Carrillo et al, 2(X)9; Grimes & Melloni, 2002;Melloni et al, 1997;Ricci et al, 2007). One putative mechanism through which adolescent AAS exposure facilitates the development of aggression is through alterations in the neural circuitry modulating this behavior.…”
Section: Discussionmentioning
confidence: 92%
“…It is interesting to note that an investigation of the onset of the neurodevelopmental effects of AAS on LAH-glutamate revealed that AAS-mediated increases in the number of glutamate fibers occur following 2 weeks exposure to AAS (Carrillo et al, 2011a). Not surprisingly is that this is the .same time point when heightened levels of aggressive behavior are first observed in adolescent AAS-treated hamsters (Grimes, Ricci, & Melloni, 2007;Melloni, Connor, Hang, Harrison, & Ferris, 1997). Together these data support the notion that adolescent AAS exposure underiies neurodevelopmental changes in LAH-glutamate, and that these changes may play a role in the emergence of the elevated aggressive phenotype.…”
mentioning
confidence: 89%